2023
DOI: 10.3390/ph16020194
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging and Kinetic Modeling of Novel Glycogen Synthase Kinase-3 Radiotracers [11C]OCM-44 and [18F]OCM-50 in Non-Human Primates

Abstract: Glycogen synthase kinase 3 (GSK-3) is a potential therapeutic target for a range of neurodegenerative and psychiatric disorders. The goal of this work was to evaluate two leading GSK-3 positron emission tomography (PET) radioligands, [11C]OCM-44 and [18F]OCM-50, in non-human primates to assess their potential for clinical translation. A total of nine PET scans were performed with the two radiotracers using arterial blood sampling in adult rhesus macaques. Brain regional time-activity curves were extracted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Unfortunately, BBB-permeable radiometabolites of [ 11 C]OCM-44 were observed in NHPs and mice. 112,115 The lead 18 F-labeled analog, [ 18 F]OCM-50 (Figure 6), demonstrated peak SUV 2.0 in both Sprague-Dawley rats and NHPs. 113 Our recent F I G U R E 6 Structures of GSK-3 PET radiotracers showing improved BBB permeability with minor structural modifications.…”
Section: Structure-activity Relationship (Sar) Studies Supported By P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, BBB-permeable radiometabolites of [ 11 C]OCM-44 were observed in NHPs and mice. 112,115 The lead 18 F-labeled analog, [ 18 F]OCM-50 (Figure 6), demonstrated peak SUV 2.0 in both Sprague-Dawley rats and NHPs. 113 Our recent F I G U R E 6 Structures of GSK-3 PET radiotracers showing improved BBB permeability with minor structural modifications.…”
Section: Structure-activity Relationship (Sar) Studies Supported By P...mentioning
confidence: 99%
“…We proceeded to develop second generation radiotracers for GSK‐3 based on PF‐367, and the highest brain uptake was observed with [ 11 C]OCM‐44 (Figure 6), which displayed a three‐fold increase in peak NHP brain uptake compared with [ 11 C]PF‐367. Unfortunately, BBB‐permeable radiometabolites of [ 11 C]OCM‐44 were observed in NHPs and mice 112,115 . The lead 18 F‐labeled analog, [ 18 F]OCM‐50 (Figure 6), demonstrated peak SUV 2.0 in both Sprague‐Dawley rats and NHPs 113 .…”
Section: Selected Examples Of Pet Radiotracers: Challenges Overcoming...mentioning
confidence: 99%
“…Smart et al. recently reported a PET study using [ 11 C]OCM‐44 and [ 18 F]OCM‐50 in nonhuman primates [87]. Both radiotracers displayed good brain uptake and distribution in gray matter; however, radiometabolite accumulation may confound image analysis [87].…”
Section: Imaging Agents For Neuroinflammationmentioning
confidence: 99%
“…[ 11 C]OCM-44 was identified as a lead Glycogen synthase kinase 3 radiotracer with optimized brain uptake by PET imaging in nonhuman primates, and further assessment revealed that [ 11 C]OCM-51 is highly potent (IC 50 = 0.030 nM) and selective (over 10-fold GSK-3β/GSK-3α) for GSK-3β [86]. Both radiotracers displayed good brain uptake and distribution in gray matter; however, radiometabolite accumulation may confound image analysis [87].…”
Section: Colony-stimulating Factor-1 Receptor (Csf-1r)mentioning
confidence: 99%
See 1 more Smart Citation